Tackling child health inequalities due to deprivation: using health equity audit to improve and monitor access to a community paediatric service. Issue 2 (2nd November 2012) - Maharaj, V.; Rahman, F.; Adamson, L.
Abstract Background Deprived children constitute a large population with high levels of ill health, and difficulty with access to healthcare contributes to their poor health outcomes. There is debate on how best to engage deprived families and the literature on differential access to paediatric care based on deprivation is limited. Aims To demonstrate that community paediatrics can contribute to reduction of health inequalities by providing services that are accessible to and preferentially used by children whose health is likely to be affected by deprivation. To provide a template for others to improve and monitor equity in their services. Method Long‐term service reconfiguration and health equity audit. We used routinely collected activity data and the Indices of Multiple Deprivation to construct equity profiles of the children using our service, and compared these with the profile of the population aged 0–16 years in the geographical area covered by the service. Results The new patient contact rate for the most deprived children in the population was more than three times that of the least deprived [odds ratio (OR) 3.29, 95% confidence interval (CI) 2.76–3.93]. Deprived children were more than twice as likely to require multi‐agency meetings as part of their medical care (OR 2.28, 95% CI 1.94–2.69). Seventy per cent (3693/5312) of our total contacts were with children in the two most deprived quintiles. There was a marked socio‐economic gradient in all types of contact. Conclusions The model of care used by our community paediatric service successfully engages deprived families, thereby reducing health inequalities due to poor access. Key features are multi‐agency working, removing barriers to access, raising staff awareness and use of health equity audit. Our findings provide support for tackling health inequalities via health services that are available to all, but capable of responding proportionately according to level of need, a model recently described as proportionate universalism.